Assess the knowledge and skills on partogram among the midwifery students in a selected Nursing college, Puducherry - Buvana, M; Bala Dash, Manju (International Journal of Nursing Research, 2023)
A descriptive study was done to assess the knowledge on skills on partogram among midwifery student at Mother Theresa Post Graduate and Research Institute of Health Sciences, Puducherry. Objective: Assess the knowledge on skill use of partogram among midwifery students and identify the challenges facing midwifery students with regards to the utilization of partogram in maternity wards and Determine the factors that influence the use (proper or not proper) of partogram among midwifery students in maternity wards methods. Methodology: A quantitative approach and descriptive non-experimental research design were used. Simple random sampling technique was used to select the sample for this study. The sample size was 76. Data were collected by using modified WHO partograph tool followed by self-structured questionnaire was provided and one scenario was given to each and every student to assess how they are plotting the partograph. The researcher collected the data individually after obtaining consent from each participant. The inclusion criteria were those who are willing to participate and present during the day of data collection. After the data collected it was entered in the X-cel sheet and coding was given for better analysis. The data was analyzed both descriptive and inferential statistics method. Demographic variables are planned to analyze by frequency and percentage and the knowledge, skill aspects were analyzed with the help of descriptive as well as inferential statistics. Results: The results highlighted that all most all 76(100%)students aware about partogram but regarding the utilization in the labor room only 59(77.63%) students said that they use regularly whereas 17(22.36%) said that they use very rarely.